Developing an innovative stiffened shear damper for concentrically braced frames. (April 2023) - Ghamari, Ali; Alzeebaree, Radhwan; Thongchom, Chanachai
Highlights: A new damper has been introduced with ease to build and replace after a severe earthquake. It acts as a ductile fuse with a high rotation capacity without fracturing. It does not face any degradation in case of strength, stiffness, and energy absorption. The required equation for the design of the damper has been presented. Abstract: Although the concentrically braced frame (CBF) systems pertain high elastic stiffness and lateral strength, they reflect a low seismic energy absorption capacity. This is due to the buckling of CBF's diagonal member under compressive loading. To overcome this, researchers have proposed the use of several types of dampers to improve the seismic behavior of the CBF systems. Among them, the metallic shear damper is the most popular due to its suitable performance characteristics. To overcome the low stiffness characteristics of shear dampers, strengthening the shear damper with X-stiffeners is proposed and the performance is evaluated numerically and parametrically in this paper. Results indicated that by adding the X-stiffeners, the ultimate strength and elastic stiffness of the shear dampers are enhanced, considerably. But, we found that the properties of the stiffeners do not impact the stiffness at rotation greater than 0.5%. The behavior of dampers is affected by some parameters such as the ratio of the strength of the web plate to the flange plate, and the ratio of the X-stiffener strength to the flange plate strength. Thus, to predict the behavior of the damper accounting for the parameters, modified equations are proposed. The results highlighted a good agreement between the proposed modifications and finite element modeling.